Back Cover: A Karplus Equation for the Conformational Analysis of Organic Molecular Crystals (Angew. Chem. Int. Ed. 45/2019). Issue 45 (18th September 2019) - Thureau, Pierre; Carvin, Isaure; Ziarelli, Fabio; Viel, Stéphane; Mollica, Giulia
Abstract : Solid‐state NMR spectroscopy can be used as a molecular goniometer for organic solids. In their Communication on page 16047 ff., G. Mollica et al show that dihedral angles in organic solids are related to three‐bond 13 C‐ 13 C scalar couplings through a simple Karplus equation, thereby allowing molecular conformation in the solid state to be determined by NMR spectroscopy. These findings open new avenues for the atomic‐level structure determination of materials that exist as powders.